2020
DOI: 10.2174/1573397115666191018162606
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Ankylosing Spondylitis: Relationship with Disease-Related Variables

Abstract: Background: Ankylosing spondylitis (AS) is a chronic progressive inflammatory disease leading to functional limitations and subsequently impaired quality of life (QoL). Despite the fact that QoL was recognized as a significant perception, it was excluded from the core domains (defined by the Assessment of Spondyloarthritis International Society), because of the ambiguity of measurement choice. Aim: To assess QoL in patients with AS using a generic; Short Form-36 (SF-36) and a disease-specific; Ankylosing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…We have demonstrated that the group of patients with a peripheral form of disease tended to have reduced life quality indices compared with those of patients with a central AS form, by the SF-36 (PCS; MCS) and HAQ. Similar results were registered by G. Elolemy et al (2020): patients with a peripheral form of disease had a worse life quality than those with a central AS form in terms of the physical component [3]. However, W. Hamdi et al (2012) did not find any associations with a form of disease [18].…”
Section: Note: Pf-physical Functioning; Rp -Role-physical Functioning; P -Pain; Gh-general Health; Vt -Vitality; Sf -Social Functioning; supporting
confidence: 65%
See 1 more Smart Citation
“…We have demonstrated that the group of patients with a peripheral form of disease tended to have reduced life quality indices compared with those of patients with a central AS form, by the SF-36 (PCS; MCS) and HAQ. Similar results were registered by G. Elolemy et al (2020): patients with a peripheral form of disease had a worse life quality than those with a central AS form in terms of the physical component [3]. However, W. Hamdi et al (2012) did not find any associations with a form of disease [18].…”
Section: Note: Pf-physical Functioning; Rp -Role-physical Functioning; P -Pain; Gh-general Health; Vt -Vitality; Sf -Social Functioning; supporting
confidence: 65%
“…However, they are significantly worse in subjects with the Vitamin D deficiency, a high dose of glucocorticoids and high disease activity. http://pjs.zaslavsky.com.ua Оригінальні дослідження / Original Researches life quality compared to the general population; however, the patients with comorbidities register an even more reduced one [2,3]. In particular, according to Shevchuk S. et al (2020), the life quality evaluated by the SF-36 and HAQ questionnaires was significantly lower in the AS patients with an anemic syndrome than in the patients with no anemia present [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ankylosing spondylitis can negatively impact the patient's quality of life [78,79]. In addition to objective measures of disease control, there are various patient-reported outcomes (PROs) that measure subjective improvements in the disease process.…”
Section: Targeting Il-17 In Ankylosing Spondylitis and Psoriatic Arth...mentioning
confidence: 99%
“…Construct validity has been demonstrated because the ASQoL correlates with the BASDAI (0.42), BASFI (0.51), and Bath Ankylosing Spondylitis Metrology Index (BASMI) (0.48) (95). The ASQoL is also correlated with the Jenkins Sleep Scale (96).…”
Section: Ankylosing Spondylitis Quality Of Life Indexmentioning
confidence: 99%